Saudi EFL Students’ Perceptions of Pedagogical Translanguaging in English Medium Instruction - Almatrafi, Bakheet (International Journal of Language and Literary Studies, 2023)
The English language has been increasingly used as a medium of instruction (EMI) at the tertiary level in Saudi Arabia. Recent research has garnered Saudi students’ perceptions regarding EMI, revealing that some participants preferred a mixture of English and Arabic. Although these studies have provided valuable results, they did not expose participants to translanguaging before investigating their perceptions. Hence, this paper reports on the findings of a quantitative study that surveyed 18 Saudi college students about their perceptions of a four-week pedagogical translanguaging intervention delivered to improve their academic writing skills. The purpose of this study is to investigate the effectiveness of incorporating pedagogical translanguaging into an EMI setting. A Likert-scale questionnaire consisting of 12 items was used to collect data after which it was analyzed via SPSS. Findings revealed most participants found translanguaging useful as it made lessons and activities less challenging and more comprehensible. We suggest that teachers and policymakers adopt a flexible language use policy in tertiary education, normalizing translanguaging as a medium of instruction in EMI contexts. Implications for incorporating translanguaging as a medium of instruction and recommendations for future research directions are discussed.